"Just Doing a Favor for a Friend": The Social Supply of Ecstasy Through Friendship Networks. (July 2017) - Bright, David A.; Sutherland, Rachel
The current project focused on the "not for profit" supply of illicit drugs within social networks. The aims of the study were to (a) explore the characteristics of social supply of ecstasy and the typical ways in which social dealing occurs, and (b) explore the benefits of social supply as perceived by those who engage in social supply. Overall, the results suggest that social supply of ecstasy occurs in dense, closely knit friendship networks and that mutual supply may be common. Users within friendship networks source ecstasy independently and concurrently supply to members of the group to ensure consistent supply of quality product and to minimize risks of health harms and criminal justice consequences. Social dealing produces little or no financial profit, yet the majority of participants in this study purchased ecstasy in amounts that expose them to significant criminal justice penalties.